International Vat Harmonization : Economic Effects - Frenkel, Jacob (IMF Working Papers; Working Paper ;, 1991)
This paper highlights key macroeconomic issues related to VAT harmonization. A model is developed which emphasizes the effects of changes in the time profile of various taxes on international behavior. Dynamic simulations reveal that the macroeconomic and welfare implications of VAT harmonization, including conflicts of interest, depend critically on the tax system and the degree of substitution governing temporal and intertemporal allocations. We also demonstrate that the effects of revenue-neutral tax conversions between income and consumption tax systems undertaken by a single country depend critically on international differences in behavior.